2018
DOI: 10.1007/s11999.0000000000000051
|View full text |Cite
|
Sign up to set email alerts
|

The Safe Zone Range for Cup Anteversion Is Narrower Than for Inclination in THA

Abstract: Level III, diagnostic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
83
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(92 citation statements)
references
References 39 publications
4
83
1
1
Order By: Relevance
“…Cup malposition, with respect to the Lewinnek safe zone, is an independent risk factor for postoperative dislocation (odds ratio 1.88) [17]. Because the safe zone for cup anteversion is narrower than that for inclination [4], the angle of anteversion must be carefully determined. When THA is performed in the supine position, cup alignment can be monitored with the use of intraoperative fluoroscopy or X-ray.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cup malposition, with respect to the Lewinnek safe zone, is an independent risk factor for postoperative dislocation (odds ratio 1.88) [17]. Because the safe zone for cup anteversion is narrower than that for inclination [4], the angle of anteversion must be carefully determined. When THA is performed in the supine position, cup alignment can be monitored with the use of intraoperative fluoroscopy or X-ray.…”
Section: Discussionmentioning
confidence: 99%
“…Correct implant positioning is important for good longterm results in total hip arthroplasty (THA). Inadequate orientation of the acetabular component is associated with postoperative impingement [1], dislocation [2], accelerated polyethylene wear [3], liner damage, and restricted range of motion [4]. Surgeons use intraoperative navigation systems to improve the accuracy of implant orientation [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It was previously proved, that proper prosthesis implants placement might be crucial for lowering the possibility of postoperative hip dislocations. (11,12) Still, to our knowledge there are no systematic reviews covering this subject, and while there is still unsatisfactory evidence concerning long-term outcomes of DAA, such review may prove useful in the debate. There has been recently published meta-analysis of 13…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have attempted to improve the predictive efficacy of coronal safe zones. [14][15][16] Originally, Elkins and colleagues 14 proposed narrowing the coronal safe zone inclination and anteversion from 37 o -46 0 and 12 o -22 0 , respectively. Tezuka et al 16 reported that using this method resulted in fewer hips implanted into the narrow safe zone but no change in the number of hips in the functional safe zone.…”
Section: Discussionmentioning
confidence: 99%